2007
DOI: 10.2214/ajr.05.0512
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CT for Detecting Small Hepatocellular Carcinoma: Usefulness of Delayed Phase Imaging

Abstract: Delayed phase imaging is useful for detecting small HCCs and should be included in dynamic CT examinations of patients with liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 29 publications
3
47
2
4
Order By: Relevance
“…This "washout" may be more conspicuous in the delayed compared with the portal venous phase, and in some lesions, "washout" may be depicted only in the delayed phase (53,54). The mechanisms underlying washout appearance in HCC are not fully understood.…”
Section: Diagnosis and Staging Of Hcc With Extracellular Agentsmentioning
confidence: 99%
“…This "washout" may be more conspicuous in the delayed compared with the portal venous phase, and in some lesions, "washout" may be depicted only in the delayed phase (53,54). The mechanisms underlying washout appearance in HCC are not fully understood.…”
Section: Diagnosis and Staging Of Hcc With Extracellular Agentsmentioning
confidence: 99%
“…In fact, advances in cross-sectional imaging have led to a drastic limitation in the requirement for biopsy of focal lesions in the cirrhotic liver [6,7] . In this setting, good quality contrast enhanced computed tomography (CT) and magnetic resonance imaging (MRI) are generally highly accurate for the diagnosis of HCC [8,9] . However, biopsy remains very important in patients with a liver nodule without typical radiological features (hypervascularization in arterial phase followed by venous wash-out in portal/venous phase) [5,10] , or when α-fetoprotein levels are not diagnostic of HCC (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with previous study; the small size HCC lesions < 2cm 2 mostly appear as hyper-dense in the arterial and venous phase because the blood supply was so good enough with minimum necrotic tissues. In such realm Monzawa et al [24], found that some HCCs, especially small or well-differentiated lesions, may not be hyper-enhancing on arterial phase images, and only 58% of HCCs < 2 cm were hyper-vascular on the arterial phase. Conversely, a minority of hypervascular HCCs may not exhibit washout on portal venous or delayed phase image; as has been stated by Lee et al [25].…”
Section: Resultsmentioning
confidence: 99%